From the "what" to the "how": Teaching integrative medicine-related skills to medical students during COVID-19. Issue 7 (July 2022) - Samuels, Noah; Shaham, Dorith; Schiff, Elad; Ben-Yehuda, Dina; Finkelstein, Adi; Lesser, Lior; Bergel, Michael; Reis, Shmuel; Ben-Arye, Eran
Abstract: Objective: To examine the impact of an integrative medicine (IM) course on self-perceived IM-related communication and research skills. Methods: A 3-day mandatory "hybrid" (online and in-person) IM course was held within COVID-19 restrictions for 161 pre-clerkship medical students, with workshops facilitated by mentor healthcare professionals (IM and non-IM) and student-directed tasks. Self-perceived levels of 6 IM-related skills were scored (from 1 to 5) for history-taking; communicating with patients with "alternative" health-beliefs; referral to IM consultations; assessing risks/benefits; and working with non-medical IM practitioners. Results: 137 students (85.1%) completed pre-/post-course questionnaires, with overall scores improving from pre-course (1.98 ± 0.92) to post-course (3.31 ± 0.63; p < 0.0001), for the entire group and student subgroups (with vs. without prior IM experience). Multivariate analysis found no association between age, gender, primary language or prior experience with IM and improvement in skill scores. Conclusions: The IM course increased self-perceived skill levels, reflecting the course curriculum and workshops. Further research needs to explore the application of these skills during clinical training. Practice implications: Teaching medical students about IM in a course comprising communication and research skills was shown to be feasible and effective. The application of IM-related skills needs to be evaluated during the clinical clerkship. Highlights: We examined the impact of a pre-clerkship course for medical students on integrative medicine (IM). The course included online teaching and mentor-facilitated workshops and discussions by IM/ non-IM healthcare professionals. It improved IM-related history-taking, communication, referral, risk-benefit assessment, and working with IM practitioners. Future research needs to assess implementation of IM-related skills during clinical training.